2021
DOI: 10.1111/jgs.17147
|View full text |Cite
|
Sign up to set email alerts
|

Advance care planning by proxy in German nursing homes: Descriptive analysis and policy implications

Abstract: Background: Legally recognized advance directives (ADs) have to be signed by the person to whom the decisions apply. In practice, however, there are also ADs written and signed by legal proxies (surrogates) on behalf of patients who lack decision-making capacity. Given their practical relevance and substantial ethical and legal implications, ADs by proxy (AD-Ps) have received surprisingly little scientific attention so far.Objectives: To study the form, content, validity, and applicability of AD-Ps among Germa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…However, all parties reported these processes to be highly variable, with a lack of standardization in terms of the content of discussions with health care proxies, the timing of these discussions, the types of decisions which are made, the types of information that are documented, and the forms on which these decisions are documented. These variable practices are consistent with the findings in other countries, such as Australia [ 26 ] and Germany, where document analyses have shown variation in types of decisions, presence of proxy and physician signatures and ethical justifications [ 27 ]. This variability reflects the willingness of health professionals to engage in developing their processes within each institution, but this also poses problems for the transmissibility of information and coordination, especially in case of hospital transfer.…”
Section: Discussionsupporting
confidence: 87%
“…However, all parties reported these processes to be highly variable, with a lack of standardization in terms of the content of discussions with health care proxies, the timing of these discussions, the types of decisions which are made, the types of information that are documented, and the forms on which these decisions are documented. These variable practices are consistent with the findings in other countries, such as Australia [ 26 ] and Germany, where document analyses have shown variation in types of decisions, presence of proxy and physician signatures and ethical justifications [ 27 ]. This variability reflects the willingness of health professionals to engage in developing their processes within each institution, but this also poses problems for the transmissibility of information and coordination, especially in case of hospital transfer.…”
Section: Discussionsupporting
confidence: 87%
“…A written condensation of the “attitudes” forms the AD’s base for documenting concrete treatment preferences in three distinct clinical scenarios: (1) treatment preferences in an emergency (documented on a Physician’s Order for Life-Sustaining Treatment in Case of Emergency (POLST-E)), (2) treatment preferences for hospital care in case of an incapability to consent of uncertain duration, and (3) treatment preferences for a possible future permanent incapability to consent. In surrogate decision-making, besides the “attitudes” two concrete scenarios are documented in the AD-P form: (1) emergency preferences as in the AD, and (2) treatment preferences in case of future severe functional or emotional deterioration [ 32 34 ] see Additional file 1 (selected intervention details).…”
Section: Interventionsmentioning
confidence: 99%
“…Despite these substantial benefits, international evidence has shown that many care home residents do not have an ACP (Batchelor et al, 2019;Detering et al, 2010;Garden et al, 2022;In der Schmitten et al, 2021;Jennings et al, 2016). Batchelor et al (2019) attributed the low prevalence of ACPs to a lack of knowledge and education on the part of care home staff, including uncertainty regarding the legal status of care plans.…”
Section: Introductionmentioning
confidence: 99%